Pengaruh The Effect of the Audio-Visual-Based E-Book Suara Alamku on Improving Learning Learning Activity in Indonesian Language - Maria Goreti Rini Kristiantari; Chindytia; Ni Putu Raina Cantika Dewi; Ni Putu Raini Dewi Lestari (Undiksha Press, 2025)
The low level of student engagement in Indonesian language subjects at the primary school level poses a challenge that must be addressed to improve the quality of learning. This study aims to examine the effectiveness of audiovisual-based e-book media in enhancing students' learning activeness. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two sessions. The subjects of this study were 27 fourth-grade primary school students. Data were collected through writing tests and teacher and student observation sheets. Data analysis was carried out using both qualitative descriptive and quantitative approaches. The results showed an increase in student learning activeness from an initial condition of 26%, rising to 48% in Cycle I Session I, 67% in Cycle I Session II, 74% in Cycle II Session I, and reaching 85% in Cycle II Session II. These findings indicate that audiovisual-based e-book media significantly enhances student engagement during the learning process. This media has proven effective in capturing attention, increasing participation, and facilitating contextual understanding of the material. The implications of this study suggest that the use of interactive digital media can serve as an innovative alternative in teaching Indonesian language in primary schools.